Electromechanical properties of polyimide composites containing titanium dioxide nanotubes. (August 2015) - Hamciuc, Elena; Ignat, Mircea; Hamciuc, Corneliu; Stoica, Iuliana; Dimitrov, Lubomir; Kalvachev, Yuri; Olariu, Marius
Polyimide composite films were prepared by casting solutions resulting from direct mixing of a poly(amic acid) and titanium dioxide (TiO2 ) nanotubes (TNTs) onto glass plates, followed by thermal imidization. TNTs with outer diameters of approximately 10–12 nm and length of several hundreds of nanometers were synthesized by the hydrothermal method. The morphology of the nanotubes was investigated by using high-resolution transmission electron microscopy. The influence of TNTs content on structural, thermal, and electromechanical properties of pure polyimide and composite films was studied. The scanning electron microscopy and atomic force microscopy showed good compatibility between TNTs filler and polyimide matrix. The value of average roughness of film surface increases with increasing the content of TNTs. The films were flexible, tough, and exhibited high thermal stability. A study of microelectromechanical properties of these films was performed. The films showed nanometric displacements in the range of 250–800 nm when an electric voltage of 500 V was applied on their surface.